2019
DOI: 10.1111/ejh.13202
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal disease in patients undergoing umbilical cord blood transplantation after myeloablative conditioning regimen

Abstract: Objective Characteristics and risk factors (RFs) of invasive fungal disease (IFD) have been little studied in the setting of umbilical cord blood transplantation (UCBT). Method We retrospectively included 205 single‐unit myeloablative UCBT recipients with a median follow‐up of 64 months. Results Fifty‐six episodes of IFD were observed in 48 patients (23%) at a median time of 123 days after stem cell infusion. Invasive mold disease (IMD) occurred in 42 cases, 38 of them (90%) caused by invasive aspergillosis wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Overall mortality in this study was 56% in the first year and were primarily related to infectious outcomes 7 . Furthermore, a retrospective review 45 evaluating 205 patients who received a single‐unit UCBT demonstrated a 23% incidence of IFI with 63% occurring within the first 6 months post UCBT. The cumulative incidence of IFI at 1 year was 20% and 25% at 5 years.…”
Section: Fungal Infections In Alternative Donor Transplantmentioning
confidence: 68%
See 1 more Smart Citation
“…Overall mortality in this study was 56% in the first year and were primarily related to infectious outcomes 7 . Furthermore, a retrospective review 45 evaluating 205 patients who received a single‐unit UCBT demonstrated a 23% incidence of IFI with 63% occurring within the first 6 months post UCBT. The cumulative incidence of IFI at 1 year was 20% and 25% at 5 years.…”
Section: Fungal Infections In Alternative Donor Transplantmentioning
confidence: 68%
“…The cumulative incidence of IFI at 1 year was 20% and 25% at 5 years. Seventy‐three percent of patients died in this study, with fungal infection being the primary cause in 22% of patients with a median time of 172 days 45 . Aspergillosis was the most common IFI and majority of patients were receiving mold‐active prophylaxis with voriconazole but at a reduced dose of 100 mg/day, which is lower than standard dosing 45 …”
Section: Fungal Infections In Alternative Donor Transplantmentioning
confidence: 85%
“…From March 2014, antifungal prophylaxis consisted of micafungin (50 mg/day iv) from the start of the conditioning regimen until neutrophil recovery and switched to posaconazole 300mg daily in tablets until day + 100 or while on steroids to treat moderate‐to‐severe GvHD. At HLF, from January 2010 to December 2016 antifungal prophylaxis was based on fluconazole (100 mg/day) from the start of conditioning until the day of stem cell infusion (day 0) and voriconazole 100 mg/BID a day thereafter until day + 100 or while on steroids . In January 2017, antifungal prophylaxis was changed and consisted of fluconazole (100 mg/day) during conditioning until day + 7 and posaconazole (300 mg/day) thereafter until day + 100 or while on steroids.…”
Section: Methodsmentioning
confidence: 99%
“…CMV infection Reactivation of herpesviruses or respiratory viruses may induce local and systemic immunosuppression, increasing the risk for secondary bacterial and fungal infections, including IFD relapse. CMV in particular, as CMV organ disease 27,33,52,53 or even CMV reactivation, 54,55 has been associated with increased risk of both new and relapsed IFDs post-HSCT. 56 Apart from the deleterious effect of CMV viremia on innate immunity, these patients often have other risk factors for a new-onset or relapsed IFD, such as the use of glucocorticoids, prolonged lymphopenia, and/or GVHD.…”
Section: Viral Infections As Risk Factors For Ifd Relapsementioning
confidence: 99%